2016
DOI: 10.1007/s11250-016-1155-x
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of ruminant brucellosis in central-eastern Tunisia

Abstract: In this study, we conducted an investigation to determine the true prevalence of bovine and ovine brucellosis in central-eastern Tunisia. A total of 1134 veterinary samples taken from 130 ruminant herds were screened for brucellosis using IS711-based real-time PCR assay. Sera collected from the ruminants were tested using the Rose Bengal test and indirect enzyme-linked immunosorbent assay. Based on serological and molecular results, the true adjusted animal population level prevalence was 23.5 % in cattle, aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our results have shown that the probability of having a positive animal was higher in urban (17%) than in peri‐urban (5.26%) and rural (11.1%) areas. This could be explained by the fact that most dairy farmers practicing the intensive farming are situated in urban areas where there is a high demand for milk (Barkallah et al., ; Jaouad, ). In this type of areas, reproductive infections associated with Chlamydiae , particularly abortions, appear mainly as enzootic diseases, resulting in severe economic losses (Igayara‐Souza et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results have shown that the probability of having a positive animal was higher in urban (17%) than in peri‐urban (5.26%) and rural (11.1%) areas. This could be explained by the fact that most dairy farmers practicing the intensive farming are situated in urban areas where there is a high demand for milk (Barkallah et al., ; Jaouad, ). In this type of areas, reproductive infections associated with Chlamydiae , particularly abortions, appear mainly as enzootic diseases, resulting in severe economic losses (Igayara‐Souza et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…During this study, many geographical regions of Sfax have been visited as described by Barkallah et al. (). In each region, households owning cattle and/or sheep were identified through discussion with responsible veterinarians during the annual vaccination campaigns.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations